Mesenteric Lymphangioma – a Rare Tumor of the Abdomen - Florin BOBIRCA; Ionut MELESTEU; Dan DUMITRESCU1; Carmen IORGUS; Romina Marina SIMA; Traian PATRASCU; Anca BOBIRCA (Modern Medicine)
Mesenteric lymphangioma (ML) is a cystic tumor developed at the base of the mesentery, which occurs frequently in children, rarely in adults, with nonspecific symptoms, often diagnosed late. The diagnosis is made by computer tomography and the curative treatment is the surgical one with good results and with optimal postoperative outcome. A 44-year-old patient for whom mesh surgery for incisional hernia post appendectomy has been performed was admitted to our clinic for nonspecific gastrointestinal symptoms for which he has also been investigated multiple times in other services. On the right flank and iliac fossa, a tumor of firmelastic consistency is detected, relatively well delimited. Computed tomography (CT) describes the lesion as a mesenteric tumor. Intraoperatively, a cystic tumor is detected, which is punctured, the biochemical result highlighting the lymphatic character. The surgical treatment was represented by segmental intestinal resection with entero-enteroanastomosis. No postoperative events were reported.